2011
DOI: 10.1002/jez.680
|View full text |Cite
|
Sign up to set email alerts
|

High genetic differentiation among populations of the small cavy Microcavia australis occupying different habitats

Abstract: The small cavy Microcavia australis, a social and fossorial rodent, inhabits a large distribution range in South American arid zones. The species is versatile in coping with the seasonal and spatial variability typical of these environments through changes in morphology, physiology, and behavior. In order to explore whether phenotypic variations are related to the evolutionary history of the species, we analyzed the levels of genetic variability and divergence among four populations that differ in climate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In this study, it is not unexpected that 26 different haplotypes were found coupled with high haplotype diversities (0.85 -0.97) across the three zones, owing to the fact that the D-loop has a high mutation rate [21]. These results are comparable to a previous report on a South American hystricomorph rodent, Microcavia australis [37] which indicated 0.70 -0.93 for haplotype diversity (h) and 0.0006 -0.0095 for nucleotide diversity (π). The results of our study are however higher than that of [38] on Laonastes aenigmamus in Laos (h = 0.79).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, it is not unexpected that 26 different haplotypes were found coupled with high haplotype diversities (0.85 -0.97) across the three zones, owing to the fact that the D-loop has a high mutation rate [21]. These results are comparable to a previous report on a South American hystricomorph rodent, Microcavia australis [37] which indicated 0.70 -0.93 for haplotype diversity (h) and 0.0006 -0.0095 for nucleotide diversity (π). The results of our study are however higher than that of [38] on Laonastes aenigmamus in Laos (h = 0.79).…”
Section: Discussionsupporting
confidence: 89%
“…Also, genetic drift, dispersal pattern and vicariance events such as habitat fragmentation may all influence genetic structure and diversity of mammals. For instance [37] found highly differentiated highland and lowland populations of M. australis with almost all haplotypes being unique to populations, indicating very restricted levels of gene flow between the populations. Similar results were obtained by Ojeda [40] on another rodent, Tympanoctomys barrerae, in the same region.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous biological or ecological researches on current small mammals have been performed in this region (Gonnet and Ojeda, 1998;Rosi et al, 2000Rosi et al, , 2003Braun and Mares, 2002;Pardiñas et al, 2010;Novillo, 2011;Rodríguez, 2011;Sassi et al, 2011;Taraborelli et al, 2011;Novillo and Ojeda, 2014; among others). These contributions provide information about different species concerning their distribution, physiological and behavioral aspects, and habitat and food preferences, essential knowledge for the analysis of paleoenvironmental aspects linked to the assemblages under study.…”
Section: Introductionmentioning
confidence: 99%